Genetic characterization of hill cattle of Himachal Pradesh using molecular markers - Kailash Mahajan,; OP. Kaila,; S. C. Gupta,; Sanjeet Katoch,; K. Gupta, (Journal of Livestock Biodiversity, 2025)
DNA from 50 randomly selected blood samples of hill cattle of Himachal Pradesh (H.P) was extracted as per Johns' method with modification. The Hill cattle contribute about 43.53% of the total Livestock population of H.P. The animals are small sized, tough, fit for hilly terrain, adapted to cold and harsh climate, disease resistant and thrive on poor pastures and nutrients. Diversity analysis was carried out using fourteen microsatellite markers. The microsatellite loci were amplified from genomic DNA samples by PCR. The PCR products for different microsatellite loci were resolved on 6% denaturing (urea) polyacrylamide gels along with 10 bp DNA ladder at 80 W (1600-2500 V). Microsatellite alleles were visualized by silver staining. The diversity parameters were estimated through PopGene Programme. The mean observed and effective numbers of alleles were 4.71+1.64 and 2.93±1.16, respectively across all loci. A total of 66 alleles were observed in hill cattle with maximum alleles (8) contributed by locus HAUT-27 and the least alleles (2) by ETH-3. The average heterozygosity was 0.43±0.26 across all loci. The observed and expected heterozygosity (0.96 and 0.84 respectively) were highest for ETH-185 and BM-1824 locus and least (0.06 and 0.17, respectively) for ETH-225 and ETH-152 locus. Except ETH-03, all other microsatellites showed high levels of variability. It appears that lesser degree of genetic diversity and reduced heterozygosity in Hill cattle of HP is probably due to high level of inbreeding. The increased level of inbreeding could be due to lesser number of breeding bulls. The exchange of the males from adjacent places may assist in resolving the problem.